2019
DOI: 10.1021/acsomega.8b03600
|View full text |Cite
|
Sign up to set email alerts
|

Selective Conversion of Hemicellulose in Macroalgae Enteromorpha prolifera to Rhamnose

Abstract: Direct hydrothermal conversion (HC) of macroalgae Enteromorpha prolifera was conducted over the temperature range of 140–240 °C. At 160 °C, monosaccharides and small molecular acids began to generate. A high yield (18.8%) of monosaccharides was obtained at 180 °C, whereas 29.6% of small molecular organic acids was attained at 200 °C. Formic acid (FA) was then employed as a catalyst, which could selectively catalyze the conversion of hemicellulose at low temperature (94.1%, 140 °C). Rhamn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A study by Chi et al (25) showed that the acid extraction method produced a better yield and higher molecular weight E. prolifera polysaccharide with intense iron chelating capacity compared with their respective water and alkali methods. Apart from extraction techniques, extraction conditions, such as time, temperature, pH, the ratio of biomass amount to solvent, and the type of elution solvent could affect the chemical composition and function of polysaccharides (19,29). For example, Yuan and his colleagues evaluated the effects of extraction temperature on the monosaccharide composition of E. prolifera polysaccharides (30).…”
Section: Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Chi et al (25) showed that the acid extraction method produced a better yield and higher molecular weight E. prolifera polysaccharide with intense iron chelating capacity compared with their respective water and alkali methods. Apart from extraction techniques, extraction conditions, such as time, temperature, pH, the ratio of biomass amount to solvent, and the type of elution solvent could affect the chemical composition and function of polysaccharides (19,29). For example, Yuan and his colleagues evaluated the effects of extraction temperature on the monosaccharide composition of E. prolifera polysaccharides (30).…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Although E. prolifera tide put a threat to the marine ecosystem, it has been used as traditional medicine and functional food (13)(14)(15)(16)(17). Recently, the nutritional composition and safety of E. prolifera have been investigated, and has been found that E. prolifera contains essential nutrients such as carbohydrate (43-51%), protein (26-33%), fat (0.2-0.8%), total amino acid (20.26-23.32%), ash (13-14%) and iron (1.1-3.4mg/g) (18), of which carbohydrate is the most abundant component (19). Furthermore, health risk assessment studies showed that the level of major micropollutants such as heavy metals, pesticides, and polycyclic aromatic hydrocarbon in E. prolifera is below the limit to cause health hazards and thus can be regarded as safe for human consumption (18).…”
Section: Introductionmentioning
confidence: 99%
“…E. prolifera is one kind of green algae and the dominant species of green tides in the Yellow Sea of China [4]; its main component is polysaccharide [5]. Previous studies have shown that the polysaccharide has many biological activities, such as hypoglycemia [6][7][8], hypolipidemic [9,10] and immunomodulatory activity [11,12], antioxidant [13,14], gut microbiota modulation [15], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis of algal polysaccharides is usually carried out in the presence of acidic catalyst, such as Brønsted acid, metal chlorides, and heterogeneous catalysts such as HZSM-5 and Sn-Beta. Over these catalysts, highly selective chemicals such as rhamnose, 5-HMF, levulinic acid or lactic acid are formed [150][151][152][153][154]. 5The research of algal biorefinery should also focus on improvement of the process, in order to realize the commercialization and industrialization.…”
Section: Discussionmentioning
confidence: 99%